THE INFLUENCE OF CO-BRANDING MAKE OVER X NIKI PRODUCTS ON THE BRAND IMAGE MAKE OVER COSMETICS ON INSTAGRAM - Galuh Sukma Dwijayanti; Mentari Anugrah Imsa; Asep Soegiarto; Qoryna Noer Seyma El Farabi; Wina Puspita Sari (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
This study explores the influence of the co-branding strategy between Make Over Cosmetics and Indonesian singer NIKI on the brand image of Make Over Cosmetics as portrayed on Instagram. In the increasingly competitive Indonesian cosmetics market, innovative marketing strategies such as co-branding play a crucial role in shaping and strengthening brand perception. This research specifically examines consumer responses to the Make Over X NIKI collaboration featured on the @makeoverid Instagram account. Utilizing a quantitative approach, the study surveyed 342 followers of the account who had interacted with content related to the co-branded product launch. Data were collected through questionnaires and analyzed using SPSS version 29 through correlation, regression, and classical assumption tests. Findings indicate that co-branding exerts a positive and significant effect on brand image, with a coefficient of determination (R²) of 0.415, suggesting that 41.5% of the variance in brand image is explained by the co-branding variable. The collaboration successfully conveyed a premium and differentiated brand image, aligning with Make Over's motto “Beauty Beyond Rules.” NIKI’s personal brand, global reach, and values reinforced Make Over’s positioning in the market. Through the Elaboration Likelihood Model (ELM), the study highlights the effectiveness of peripheral cues, such as celebrity appeal and aesthetic visuals, in enhancing brand perception on social media. The study concludes that co-branding with suitable influencers significantly strengthens brand image and recommends similar strategies for local beauty brands aiming to compete in digital and global markets.